EVOLUTIONARY APPROACH TO DETERMINATION OF STRUCTURE OF TAX SYSTEM - Nathalie V. Yurchenkova (Статистика и экономика)
Capacity of national tax systems isn’t fully revealed across all countries. Problems with tax administration, tax avoidance, leaving from the taxation of corporations and the leading financial organizations in the offshore confirm adaptation hypothesis stating that taxpayers adapt for changes in times quicker and more qualitatively than the state institutes. The leading role in formation of an evolutionary paradigm of the taxation belongs now to tools of evolutionary dynamics at social level.